2013
DOI: 10.1371/journal.pone.0068456
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Connexin Expression, Degradation and Localisation Are Regulated by Gonadotropins during the Early Stages of In Vitro Maturation of Swine Oocytes

Abstract: Gap junctional communication (GJC) plays a primordial role in oocyte maturation and meiotic resumption in mammals by directing the transfer of numerous molecules between cumulus cells and the oocyte. Gap junctions are made of connexins (Cx), proteins that regulate GJC in numerous ways. Understanding the dynamic regulation of connexin arrangements during in vitro maturation (IVM) could provide a powerful tool for controlling meiotic resumption and consequently in vitro development of fully competent oocytes. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 93 publications
1
27
0
7
Order By: Relevance
“…Two factors should be taken into account. First, our results support the hypothesis that in swine, spontaneous resumption oocyte meiosis or GVBD is substantially slower than in any other mammal (Santiquet, Robert, & Richard, ), and the greatest maturation occurs in the presence of Gns. Second, our results suggest that the presence of MINs themselves in the maturation medium does not improve the rate of nuclear maturation.…”
Section: Discussionsupporting
confidence: 84%
“…Two factors should be taken into account. First, our results support the hypothesis that in swine, spontaneous resumption oocyte meiosis or GVBD is substantially slower than in any other mammal (Santiquet, Robert, & Richard, ), and the greatest maturation occurs in the presence of Gns. Second, our results suggest that the presence of MINs themselves in the maturation medium does not improve the rate of nuclear maturation.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we observed that transcripts abundance of CX43 and FOXO1 increased with age in the GCs of untreated animals. These genes encode key regulators of GC function, proliferation, and survival, and their expression was shown to be regulated by FSH in different species (Ackert, Gittens, O'Brien, Eppig, & Kidder, 2001;Cunningham, Zhu, Unterman, & Hammond, 2003;Fang et al, 2015;Nuttinck et al, 2000;Santiquet, Robert, & Richard, 2013;Shen et al, 2014;Ting & Zelinski, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(), while the other four ( YWHAG/RPL4/HRPT1/PPIA ) are different. The reason we selected these seven genes for RT‐qPCR normalization is that they were reported within recent 5 years (year 2012 to 2015) (Choi et al., ; Gu et al., ; Kuchipudi et al., ; Nagyova et al., ; Park et al., ; Santiquet et al., ; Spate et al., ), comparing to the report published in year 2007 (Kuijk et al., ). In addition, YWHAG, one candidate gene included in the present study but not in Kuijk et al.…”
Section: Discussionmentioning
confidence: 99%
“…All seven candidate genes ( GAPDH, 18S, YWHAG, BACT, RPL4, HRPT1 and PPIA ) were chosen primarily based on their relatively stable expression in different types of pig tissues, cells and oocytes, as reported previously (Choi et al., ; Gu et al., ; Kuchipudi et al., ; Nagyova, Nemcova, Mlynarcikova, Scsukova, & Kalous, ; Park et al., ; Santiquet, Robert, & Richard, ; Spate et al., ). Detailed information on these genes was summarized as in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation